Huellas que no se borran. Ruptura y desdoblamiento psíquico en tres obras de Luisa Valenzuela (Altre Modernità, 2014)
The emotional rupture caused by experiences of repression, displacement and exile originates a dislocation in the identity of the subject which often leads into a schizophrenic search for a new identity.  In the process of adaptation to the new condition the characters often unfold into split subjects which cause them to act irrationally.This essay will explore the psychic transformations suffered by characters in their efforts to reconstitute a coherent and stable self in three works by Luisa Valenzuela: Novela negra con argentinos (1990), “Tiempo de retorno” (2008), and Realidad nacional desde la cama (1990). Her characters are split between the external reality and a repressed trauma, a situation where Memory and the wish to erase an unspeakable past strive to arouse into the surface of consciousness. Valenzuela’s protagonists are driven by the hidden desire to reach the Secret of their desolation. The true re-encounter and reconstitution of the Self will only be possible after the recognition of the indelible traces engraved in the collective Memory.